The m6A-related gene signature stratifies poor prognosis patients and characterizes immunosuppressive microenvironment in hepatocellular carcinoma - Ma, Ensi; Li, Jianhua; Shen, Conghuan; Gu, Yange; Zhang, Xinju; Li, Li; Zhao, Jing; Wang, Zhengxin (Frontiers in Immunology, 2023)
Background N6-methyladenosine (m6A) is the most abundant epitranscriptomic modification of RNA, which can affect RNA metabolism and protein translation. The m6A modification plays a critical role in cancer development, including hepatocellular carcinoma (HCC). Despite several m6A-related signatures in HCC, most of them lack the necessary validation and the reliability is still elusive. Methods Differentially expressed genes (DEGs) in the Cancer Genome Atlas were comprehensively analyzed to identify m6A signature associated with HCC prognosis. Gene set enrichment analysis, tumor mutation burden (TMB), immune infiltration, and therapeutic response were evaluated. Importantly, mass spectrometry proteomics and multiplex immunofluorescence assays were performed for validation. Results The m6A-related protein-coding gene signature was established, which can divide HCC into high-/low-risk subgroups with markedly different overall survival (OS) and clinical stages. Furthermore, we validated its reliability and robustness in our 101 independent HCC specimens using proteomic detection and confirmed that our signature readily identified high-risk HCC patients with 3-year survival rates of 44.1% vs. 71.8% in the low-risk group. Functional analysis indicated that the high-risk group might stimulate the cell cycle and activate oncogenic pathways such as MAPK, mTOR, and VEGF, whereas the low-risk group mainly regulated amino acid, fatty acid, and drug metabolism. Additionally, the high-risk group had more TMB, upregulated immune checkpoint molecule expression, including PD-1, CTLA4, TIM3, and LAG3, and preferentially formed an immunosuppressive microenvironment. Accordingly, potential therapeutic responses showed that high-risk patients were potentially sensitive to inhibitors targeting the cell cycle and MAPK signaling, with patients possibly benefiting from immunotherapy. Moreover, multiplex immunofluorescence assays indicated that high-risk HCC samples displayed distinct immunosuppressive features, with abundant M2-polarized macrophages and T-regulatory cell infiltration. Conclusion The m6A signature had a prominent capacity to evaluate OS and characterize the tumor immune microenvironment of HCC, which may serve as a useful approach for risk stratification management and provide a valuable clue to choosing rational therapeutic strategies.